Intranasal Testing and Treatment for Staphylococcus aureus With Intravenous Vancomycin and Intranasal Povidone-iodine Prior to Posterior Spinal Fusion: A Retrospective Cohort Study Between Two High-volume Children's Hospitals - Jason Malone, DO; Alex Lee-Norris, DO; Austin Wynn, MD; Kaitlin Maher, PA-C; John Lovejoy, III, MD; Ryan Illgenfritz, MD; Margaret Baldwin, MD; Adriana Cadilla, MD; Kathryn Farrell, MSN; Emily Craver, MS (Journal of the Pediatric Orthopaedic Society of North America)
Background: The impact of surgical site infections in spinal surgery can be profound. Several studies have demonstrated that S. aureus carriers have an increased risk of surgical site infection (SSI). The current literature shows decreased SSI in the adult population with povidine-iodine (PI) nasal treatment for decolonizing the nares of patients infected with S. aureus. The goal of this research study was to analyze the isolated effect of presurgical S. aureus nasal testing and PI application prior to spinal surgery. Methods: This is a retrospective cohort study of children 8 to 18 years of age who underwent posterior spinal fusion from 2018 to 2020 at two standalone academic pediatric hospitals. Both hospitals had the same preoperative surgical bundle except that Group B included testing for S. aureus and treatment preoperatively if positive. In addition, all patients in Group B received PI nasal decolonization on the day of surgery. Results: The overall infection rate between both hospitals was identified as 3.4%, with no difference between the two groups. The infection rate was lowest for adolescent idiopathic scoliosis, with a rate of 1.3% and highest for neuromuscular scoliosis, with a rate of 8.2%. Hospital-wide bacterial rates in Group A compared to Group B were higher for all S. aureus species (33.8% vs 30.1%, P ​= ​0.0004), methicillin-sensitive S. aureus (24.6% vs 13.1 %, P ​< ​0.001) but lower for methicillin-resistant S. aureus (9.2% vs 17%, P ​= ​0.02). Postoperative infection culture rates or bacterium types were not significantly different between the two groups. Conclusions: The treatment of patients with PI nasal decolonization in the pediatric spinal fusion cohort did not show a decrease in postoperative infections. The PI nasal testing and treatment was $308.25 per patient and $189,580.75 over the study period. Elimination of intranasal testing and S. aureus treatment result in cost savings and eliminates an unpleasant patient experience. Key Concepts: (1) The treatment of patients with povidine-iodine (PI) nasal decolonization in a pediatric spinal fusion cohort did not show a decrease in postoperative infections. (2) Elimination of intranasal testing and Staphylococcus aureus treatment in a pediatric spinal fusion cohort results in cost savings and reduces an unpleasant experience for the patient. (3) Increased surgical time during posterior spinal fusion in a pediatric cohort of patient did not lead to an increased rate of surgical site infection (SSI). (4) Across the cohort of pediatric patient undergoing posterior spinal fusion (PSF), the rate of infection for adolescent idiopathic scoliosis (AIS) patients was 1.3% compared with 8.2% infection rate in patients with neuromuscular scoliosis (NMS). Level of Evidence: Level III